THE EFFECT OF LAND USE AND COMMUNITY PARTICIPATION ON FLOOD CONTROL AT NORTH ACEH DISTRICT - Wesli Wesli; Sirojuzilam Sirojuzilam; A Rahim Matondang; Suwardi Lubis (Indonesian Journal of Geography, 2013)
This study is intended to answer the effect of land use, community participation and their relationship toflooding. The result states that land use has a direct effect to flooding with value of about -0.323, all of the land use does not have an indirect effect, therefore the total score is -0.323. Community participation for flood control has a direct effect of about 1.640. The participation does not have an indirect effect, therefore the total effect is 1.640. Community participation has a direct effect to flooding with score of -0.416. The indirect effect is 2.322, while the total effect is 1.906. Land use for flood control has no direct effect and indirect effect. Land use has a direct effect to flood with score of a bout -0.323. It does not have an indirect effect, while the total effect is -0.323. Flood control effect on flooding has a direct effect of 1.416. It does not have indirect effect, thus the total effect is 1.416. The study reveals that the land use and community participation related to flood variables have significant effect. Moreover, flood control effort also has significant effect to reduce flooding.